The Influence of Price Perception, Online Customer Reviews, and Product Quality on Consumer Purchasing Decisions - Paramita, Nirmala Anisa; Yuniarto, Galuh (Faculty of Economics and Business UNTAG Semarang, 2025)
This study aimed to determine the influence of price perception, online customer reviews, and product quality on purchasing decisions. The population comprised all 192 employees of the Central Java Provincial Department of Industry and Trade, and the sample comprised 100 respondents. The sampling technique used was purposive sampling. The data source was primary data, collected using a questionnaire. Multiple linear regression analysis was used for data analysis. The hypothesis test results showed that price perception, online customer reviews, and product quality had positive and significant effects on purchasing decisions. The coefficient of determination was 0.702, indicating that price perception, online customer reviews, and product quality accounted for 70.2% of the variance in the purchasing decision variables. The study concludes that price perception, online customer reviews, and product quality positively influenced employees' purchasing decisions in the Department of Industry and Trade. Therefore, further research is needed, particularly regarding employee digital transformation.